2021
DOI: 10.1177/0301574220982098
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Varied Positioning of Mini-screw, Anterior Retraction Hook, and Resultant Force Vector on Efficient En-Masse Retraction Using Finite Element Method: A Systematic Review

Abstract: Objective: The objective of this systematic review was to assess the available evidence to evaluate the effectiveness of en-masse retraction design with mini-screw with respect to the retraction hook and mini-implant position and height. Methods: The following electronic databases were searched till July 31, 2020: Pro-Quest Dissertation Abstracts and Thesis database Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Google Scholar, US National Library of Medicine, and National Research Register.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It was concluded that the force vector has to pass through the center of resistance. (7) In another study by Pedersen et al (8) the CR of anterior teeth was found to lie on a line 3 mm behind the distal surface of the canines. In addition Melsen et al (9) estimated that the CR of the anterior teeth is halfway between the center of resistance of the incisors and the center of resistance of the canines.…”
Section: Introductionmentioning
confidence: 90%
“…It was concluded that the force vector has to pass through the center of resistance. (7) In another study by Pedersen et al (8) the CR of anterior teeth was found to lie on a line 3 mm behind the distal surface of the canines. In addition Melsen et al (9) estimated that the CR of the anterior teeth is halfway between the center of resistance of the incisors and the center of resistance of the canines.…”
Section: Introductionmentioning
confidence: 90%